PERAN ADVOKASI ORGANISASI PPNI (PERSATUAN PERAWAT NASIONAL INDONESIA) DALAM DUGAAN TINDAK PIDANA MALPRAKTIK KEPERAWATAN - Dwight Nusawakan (STIKES Pasapua Ambon, 2019)
Introduction: In carrying out nursing practice, a nurse will face various problems experienced by a patient in terms of health problems and also a nurse will face legal problems that arise due to procedural errors that are applied in handling patients so that it will bring up the legal responsibility that must be experienced by a nurse. The role of the Indonesian national nurse union organization will provide legal protection on the part of the police in the form of information in the field of nursing of a nurse accused of a crime of malpractice. Method: This writing uses empirical legal research methods. Empirical Law Research is a legal research method that uses empirical facts derived from human behavior, both verbal behavior obtained from interviews and real behavior carried out through direct observation. Result: The role of the Indonesian National Nurse Association in providing legal protection to nurses will be very much needed in providing information on the legal problems faced by a nurse because only the Indonesian National Nurse Association is aware of the intricacies of nursing actions carried out by a nurse.